Beyond Frank Willett: The Need for Compositional Analysis of Yoruba Art Objects - Olaleye-Otunla, Olufemi Joseph; Ijisakin, Eyitayo Tolulope; Ademuleya, Babasehinde Augustine; Adeoye, Mosobalaje Oyebamiji (Richtmann Publishing, 2022)
Since the pioneering efforts of Frank Willett that examine the Yoruba arts, there remains a yearning gap to holistically investigate the material contents and classification of Yoruba art objects. For proper documentation, information and placement of Yoruba arts, the need for a scientific material compositional analysis of Yoruba arts cannot be overemphasised. This discourse employs a qualitative and evaluative mode of research to emphasize the need, importance and prospects of proper scientific material investigation of Yoruba arts. The study provides information on Frank Willett, the Yoruba people, and relevant studies on the Yoruba arts. It further discusses compositional analysis through the lens of literature, art authentication, and makes a case for authenticating Yoruba art collections. Considering the elegance and importance of African arts and antiquities, the findings of this study show that the provenance of Yoruba art objects has not received adequate attention; this has consequently resulted into illegal excavation, manipulations, and trade of Yoruba art collections. The study concludes that there is utmost importance and necessity for scientific material probing of Yoruba art, if it must go beyond the point where Frank Willett stopped. Hence, the need for all African art historical scholars to prospect for scientific probing of the material contents of Yoruba arts objects. Received: 13 January 2022 / Accepted: 28 February 2022 / Published: 5 March 2022